2015
DOI: 10.32800/abc.2015.38.0163
|View full text |Cite
|
Sign up to set email alerts
|

Reptile assemblages across agricultural landscapes: where does biodiversity hide?

Abstract: The transition from traditional to intensive farming, aimed at large–scale production, has rapidly altered agricultural landscapes, leading to the reduction and fragmentation of natural habitats and to the consequent loss of biodiversity. Herpetofauna is seriously threatened by agriculture intensification worldwide, but less is known about its distribution in agro–ecosystems, especially at field scale. We analysed reptile abundance and diversity in eight agricultural and semi–natural land uses, and inside vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 57 publications
1
20
0
2
Order By: Relevance
“…This could be due to wider activity range of reptiles (Fraga‐Ramirez, Suazo‐Ortuno, Avila‐Cabadilla, Alvarez‐Anorve, & Alvarado‐Diaz, 2017). Similar importance of seminatural vegetation in sustaining a complex reptile community has been observed earlier (Biaggini & Corti, 2015; Carpio et al., 2017). Our study underscores the importance of maintaining seminatural vegetation in landscape scale of 500 to 1,000 meter as an important conservation strategy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This could be due to wider activity range of reptiles (Fraga‐Ramirez, Suazo‐Ortuno, Avila‐Cabadilla, Alvarez‐Anorve, & Alvarado‐Diaz, 2017). Similar importance of seminatural vegetation in sustaining a complex reptile community has been observed earlier (Biaggini & Corti, 2015; Carpio et al., 2017). Our study underscores the importance of maintaining seminatural vegetation in landscape scale of 500 to 1,000 meter as an important conservation strategy.…”
Section: Discussionsupporting
confidence: 82%
“…As the results of this study show, the impact of agricultural intensification on amphibians is more pronounced compared with reptiles. Some earlier studies have reported similar results for either amphibians or reptiles and attributed such differences to either use of pesticides or loss of habitat or breeding ground (Beja & Alcaza, 2003; Biaggini & Corti, 2015; Bignal & McCracken, 1996; Cayuela et al., 2015; Hazell, Hero, Lindenmayer, & Cunningham, 2001; Mann, Hyne, Choung, & Wilson, 2009; Peltzer & Lajmanovich, 2007).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Reptiles are particularly vulnerable to land management activities (Glor et al 2001;Ribeiro et al 2009;Biaggini & Corti 2015), and localised declines in reptile biodiversity have been detected in many parts of Australia and worldwide (Sarre et al 1995;Smith et al 1996;Gibbons et al 2000;Brown 2001;Ford et al 2001;Woinarski & Ash 2002;James 2003;Brown et al 2008;Dimond et al 2012;Tolley et al 2019), suggesting that this is a widespread phenomenon. Many of these declines have been ascribed to the impacts of agriculture, particularly habitat destruction (Souter et al 2007;Tolley et al 2019) and habitat fragmentation (Sarre et al 1995;Mac & Brown 2001;Driscoll 2004;Masterson et al 2009); however, they also occur as a result of the gradual modification of habitat through overgrazing and the application of fertilisers and pesticides (Smith et al 1996;Gibbons et al 2000;James 2003;Michael et al 2008;Dorrough et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2001; Ribeiro et al . 2009; Biaggini & Corti 2015), and localised declines in reptile biodiversity have been detected in many parts of Australia and worldwide (Sarre et al . 1995; Smith et al .…”
Section: Introductionmentioning
confidence: 99%